Seroprevalence of Brucellosis Associated with Abortion among Sudanese Pregnant Women attending Omdurman Maternity Hospital, Sudan - M K, Alsadig Kabashi; E E, Ali Abdel Ghani; Modawe, Gadallah; Abuzeid, Nadir (مجلة الجزيرة للعلوم الصحية; مجلد 15 عدد 2 (2019), 2019)
Background: Human Brucellosis remains the most common zoonotic disease endemic in the Mediterranean area, Middle East, Southwest Asia, and parts of Latin America. The disease is endemic in the Sudan and was reported as early as 1908. It is a commonly misdiagnosed febrile disease with malaria and typhoid fever.  Brucellosis is a multi-systemic disease characterized with fever, osteoarticular involvement, neuropathies, chorea, and meningoencephalitis, gastrointestinal, hepatobiliary, genitourinary, musculoskeletal, cardiovascular, pleural effusion and pneumonia. Due to increase rates of spontaneous abortion, premature delivery and intrauterine infection with fetal death caused by this disease, there is need for urgent intervention to reduce maternal mortality rate and increase child survival. This study was designed to investigate the seroprevalence of Brucellosis associated abortion among Sudanese. Objective of the Study : To investigate the seroprevalence of Brucellosis associated abortion among Sudanese attending Omdurman Maternity Hospital, Sudan. Materials and Methods: A cross-sectional study was carried out among 120 pregnant women who have aborted and 21 pregnant women who have not aborted who attended Omdurman Maternity Hospital during the period from August to October (2015). Serum samples were collected to detect the presence of the Brucella anti bodies (BAbs) using Rose Bengal plate Test (RBPT) as screening test and Serum Agglutination Test (SAT) as confirmatory test. A structured questionnaires was designed to record demographical clinical data. Results: Prevalence of Brucella disease was found to be 1.7%(2/120) in pregnant who have aborted and increased significantly with milk consumption, cheese eating, and yoghurt consumption. Conclusion: These findings demonstrated the prevalence of Brucellosis associated abortion among Sudanese women, so that the coordination between medics and researchers started in this field.